Cortical plate segmentation using CNNs in 3D fetal ultrasound - Wyburd, MK; Jenkinson, M; Namburete, AIL (Springer, 2020)
As the fetal brain develops, its surface undergoes rapid changes in shape and morphology. Variations in the emergence of the sulci on the brain surface have commonly been associated with diseased or at-risk pregnancies. Therefore, the process of surface folding is an important biomarker to characterise. Previous work has studied such changes by automatically delineating the cortical plate from MRI images. However, this has not been demonstrated from ultrasound, which is more commonly used for antenatal care. In this work we propose a novel method for segmenting the cortical plate from 3D ultrasound images using three varieties of convolutional neural networks (CNNs). Recent work has found improvements in medical image segmentations using multi-task learning with a distance transform regularizer. Here we implemented a similar method but found it was outperformed by the U-Net, which was able to segment the cortical plate with a Dice score of 0.81 ± 0.06.